The civil lyrics of I. Franko, its artistic features (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article examines the artistic features of all cycles included in the collection of I. Franko “From the tops and lowlands”. It is determined that the dominant artistic means for civic lyrics of the poet are juxtaposition, parallelisms, allegorical meaning, personification, saturation with rhetorical constructions, comparisons, poetic appeals, epithets, hyperboles, repetitions, sound patterns, antonyms, synonyms, folklore elements, key words (struggle, bondage, grief, tears, blood, battle, chains, poverty, torment, crying, hard work, sadness, freedom, truth), and etc. The poet's civic lyrics are characterized by emotional saturation, passion, inner energy of striving to fight evil, social bondage, grief and humiliation of the people. The lyric “I” is a fighter for the liberty and a happy future for Ukraine and the democratic segments of the population. The civil lyrics of the poet present a number of relationships: man and society, man and nature, ideal and reality. The lyric “I” opposes the negative moral and social phenomena of the era, accuses the state system of anti-humanity, anti-nationality. The poet emphasizes on such phenomena of reality as oppression, hopelessness, poverty, grief, hunger, meanness, cynicism, disregard, back-breaking toil, etc. He urges to overcome the dominance of evil, lie, despotism and injustice in society. The bearer of positive is represented by a man of labor against the background of a generous nature in his works. Most of the civil lyrics works are imbued with tragic-dramatic pathos, which is caused by the irreconcilable conflict of the lyrical “I” with anti-human reality. Contrasts of the social life of the lower classes and pictures of humiliation of a person are inseparable from the motives of his greatness and spiritual strength, faith in a better future for the people. I. Franko's civil lyrics are characterized by ideological overtones, the leitmotif of the struggle against despotism of the upper classes, publicistic and romantic rhetoric, and a call for struggle for freedom and independence. The language of works is artistically rich and aphoristic. The poet believed in the power of the artistic word. The dominant images are images of fire, clouds, thunderstorm, rainstorm, wind, sun, stars, which grow into symbolic images in his works. The lyrics of the poet are intellectual in content, differ social optimism, belief in the victory of good over evil, light over darkness. I. Franko skillfully conveys the peculiarities of the author's worldview, and the lyrical “I” via creating associative fields.
Keywords: allegorical meaning; personification; allegory; metaphor; stylistic figures; civil lyrics